Activity-Based Costing Using Multicriteria Drivers: An Accounting Proposal to Boost Companies Toward Sustainability - Marinho Neto, Heitor F.; Agostinho, Feni; Almeida, Cecília M. V. B.; Moreno García, Roberto R.; Giannetti, Biagio F. (Frontiers in Energy Research, 2018)
Recognizing that natural environment is reaching its maximum limits in providing resources and diluting the waste generated by human production systems, efforts towards more sustainable production systems are mandatory to secure the development of future generations. For this purpose, changing the productivity model adopted by companies that are almost exclusively rooted on circulating money to generate profit, named business as usual, is an important issue. In this sense, an alternative would be establishing the relationship of stocks and flows of energy, material, and information with environmental, economic and social outcomes, thus resulting in new accounting approaches. This work aims to propose an activity-based costing (ABC) based on multicriteria drivers including economic, emissions, and emergy (with an “m”) values. The proposed ABC costing allocates each one of the multicriteria drivers into a specific part of the sustainability conceptual model, in an attempt to embrace a holistic perspective and allow for a sustainable-based decision, rather than considering purely economic drivers. The goal programming method is considered so as to support a decision based on multicriteria aspects. Results show that the proposed accounting approach known as ABCsustain allows for decisions towards a company’s sustainability by acting on both the amount and kind of a company’s product that should be managed, as well as on the effective increase of a specific company’s activity or process. The proposed ABCsustain could make the insertion of environmental issues into companies strategic planning more effective. It is expected that environmental issues go beyond a simple diagnoses and begin to be considered as action in factum in the companies’ decisions towards achieving a more sustainable world system.